Lending Practices and Their Impact on the Profitability of Nepalese Commercial Banks - Parajuli, Nabin (Kanakai Journal, 2024)
As the backbone of every national economy, the banking sector's development is one of the most important indicators of its financial growth, and analyzing its structural components is an essential first step in identifying the problems and challenges the nation faces. The objective of this study is to examine the lending practices and their impact on the profitability of Nepalese commercial banks. The study employed a a descriptive research design to analyze and interpret the results. Necessary data are taken from five banks out of twenty commercial banks that are currently operating in Nepal. It uses five years’ time frame from 2019-20 to 2023-24. Study reveals that non-performing loan has a negative impact on bank profitability. The findings also suggest that the banks of Nepal should strengthen their credit assessment and loan recovery mechanisms to minimize non-performing loans, as reducing NPLs is crucial for improving overall profitability.